The Influence Of PQ4R Strategy And Mathematical Reasoning Ability Towards Mathematical Communication Skills - Makur, Alberta Parinters (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2019)
This study was performed to examine the students’ reading and math skills that affected their mathematics achievement. The objective of this research was to know the effectiveness of reading strategy (PQ4R strategy) on mathematical communication skill based on mathematical reasoning skill.It was quantitative research using quasi-experimental method conducted at SMAN 3 Depok in 2014 with 80 samples of students selected based on their mathematical reasoning skill. Data were obtained through questions about mathematical reasoning and mathematical communication and then analyzed with two-way ANOVA. The data analysis and interpretation showed that students who were taught with PQ4R strategy had better mathematical communication skill than students who have been traditionally taught. The effect of mathematical communication skill differed depending on mathematical reasoning ability. There was a more significant difference between students with high mathematical reasoning skill and low mathematical reasoning skill for students in the treatment condition than there was for subjects in the control condition. Thus, there was an interaction between the learning strategy and mathematical reasoning skill. The findings lead to the recommendation that reading skill could be used to improve student's mathematical communication skill and would ease the mathematical learning proces.test. DOI: https://doi.org/10.31235/osf.io/6xk7b